2015
DOI: 10.1186/s12906-015-0979-7
|View full text |Cite
|
Sign up to set email alerts
|

Boiogito, a Kampo medicine, improves hydrarthrosis in a rat model of knee osteoarthritis

Abstract: BackgroundHydrarthrosis, which is associated with knee pain and limited range of motion, decreases the quality of life (QOL) of patients with osteoarthritis (OA). The Kampo medicine boiogito is prescribed for the treatment of knee OA with hydrarthrosis; however, its precise mechanisms of action remain unknown. The purposes of this study were to assess the pharmacological effects of boiogito and its mechanisms of action on joint effusion in rats with surgically induced OA.MethodsA rat OA model was produced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…FJHQT, also named Boogie in Japan, is composed mainly of the Sinomeniumstem and Astragalus root and has been reported to reduce joint effusion by suppressing the production of pro-inflammatory cytokine IL-1β and increasing the hyaluronan concentrations in the synovial fluid. [37] A recent clinical study demonstrated that oral administration of FJHQT for 12 weeks lowered the knee effusion in patients with osteoarthritis without any adverse effects. [38] In our study cohort, FJHQT was the most effective Chinese herbal formula for patients with knee osteoarthritis and lowered the risk of total knee replacement (HR: 0.68; 95% CI: 0.50–0.93).…”
Section: Discussionmentioning
confidence: 99%
“…FJHQT, also named Boogie in Japan, is composed mainly of the Sinomeniumstem and Astragalus root and has been reported to reduce joint effusion by suppressing the production of pro-inflammatory cytokine IL-1β and increasing the hyaluronan concentrations in the synovial fluid. [37] A recent clinical study demonstrated that oral administration of FJHQT for 12 weeks lowered the knee effusion in patients with osteoarthritis without any adverse effects. [38] In our study cohort, FJHQT was the most effective Chinese herbal formula for patients with knee osteoarthritis and lowered the risk of total knee replacement (HR: 0.68; 95% CI: 0.50–0.93).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, BO may possess other analgesic mechanisms in addition to the inhibition of ERK1/2 phosphorylation. Fujitsuka et al [15] reported that BO inhibited IL-1β secretion as well as joint fluid retention in the KOA rat model. Among the crude drugs present in BO, Astragalus root [31], Glycyrrhiza [32], and ginger [33] have been reported to exert analgesic effects against neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…According to oriental medicine, BO improves water metabolism and eliminates swelling and pain in the knee joint [14] and hence may prevent KOA. Oral administration of BO has been found to relieve gait pain in patients with KOA, and some basic research has reported that it suppresses the inflammatory response in the knee joint [15,16]. We had earlier clarified that BO suppressed the progression of KOA in rats with surgically induced KOA; moreover, BO could also improve locomotive function in the early stage of the disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Sinomenin, which is extracted from the Chinese plant Sinomenium acutum and has been reported to have an antiinflammatory effect [35,36], has been used for rheumatic diseases for over 2000 years [36]. Research has reported that Boiogito [37,38], a Kampo medicine, which includes sinomenin as a principle component, could reduce symptoms of osteoarthritis in humans [37,39] and rodents [40]. Moreover, another study revealed the antiinflammatory effects of Keishikajutsubuto [41].…”
Section: Kampo For Hip/knee Osteoarthritismentioning
confidence: 99%